Adolescentes referenciados na atenção básica: perfil nutricional e efeitos de programa de educação em saúde - Pereira, Aline Braido (2014)
Nutritional Health acquires great significance, especially during adolescence is a period of physical, social, economic and psychological transition. This study aimed to assess the nutritional status of adolescents residing in the area covered by a family health strategy and the effects of a program of health education on anthropometric variables and physical activities. This is a descriptive cross-sectional study and intervention with 236 teens 10-19 years of age, referenced in a Family Health Strategy of the City of Santa Maria-RS. After approval of the Ethics Committee UFSM Research identification of adolescents was conducted (through home visits and active search for community health agent), a questionnaire and anthropometric assessment was done. The intervention took place over a period of six months where form held educational activities for healthcare professionals for groups of 18 adolescents. The data will be entered in Microsoft Excel ® version 2007, and the statistical analysis in Stata 10.0. Frequency distribution, mean or median was used depending on the normality of the variables and to check the differences we used the chi-square test, two proportions test, Mann-Whitney or Kruskal Wallis Test "t"-Student Recital the level of significance of 5%. The mean age of the 236 adolescents was 13.1 (± 1.9) years, and for girls 13.3 (± 2.0) years and for boys and 12.8 (± 1.8). The mean weight and BMI varied with age, but no statistically significant difference between boys and girls, with the exception of BMI at age 11 was higher in girls. Regarding the time the boys had higher scores than girls from the age of 13 (p <0.05). 53.8% were normal weight adolescents, 30.9% underweight, overweight 15.3% (11.9% overweight and 3.4% obese). The boys had a higher percentage of underweight (38.5% to 25.0% of girls) and they more overweight (18.9% to 10.5% of boys). Educational intervention activities on a theme of health education for adolescents, in twelve meetings were held for about 2 hours, every 15 days, with group dynamics that enabled each adolescent participation through the telling of their own experiences in relation health and nutrition. Participated in the intervention of 77.8% were girls, and in the post-intervention 50.0% increased height, BMI 77.8%, 61.1% decreased body weight and waist circumference and a significant increase (p = 0.001) of the adolescents who had physical activity (33.3% to 83.3%). The results of this study allow us to conclude that the growth in weight and height of adolescents suffered no negative influence of low socioeconomic status, although there is malnutrition, especially in boys and overweight girls in a special way. The educational intervention on health care with group activity was effective both in relation to anthropometric variables of adolescents, in which there was a decrease in body weight, BMI and waist circumference and increased stature, and in motivation and achievement of activity physical, evidenced by the significant increase in the number of adolescents who practice it.